Superficial Thrombosis of Pelvic Congestion Syndrome Mimicking Pelvic Abscess - Adrian Romero (Clinical Practice and Cases in Emergency Medicine, 2019)
Pelvic congestion syndrome (PCS) is an uncommon illness that is typically diagnosed after chronic pelvic pain. We present a case of superficial thrombosis of pelvic veins from PCS that presented to the emergency department (ED) as a previous diagnosis of pelvic abscess with cellulitis. PCS was diagnosed in the ED by computed tomography after an abnormal point-of-care ultrasound. Here we describe this unusual presentation and our approach to the diagnosis.